Upaya Public Relations Melalui Customers Relations Managament Mitsubishi Suryopranoto - Putri Azzahra Fitriani; Syifa Astasia Utari (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
Maintaining good relationships with customers is a successful way for companies to retain customers, in this case it is important to pay attention to customers and know potential long-term needs so that customers remain loyal to the company. This research aims to find out how Public Relations Efforts through Mitsubishi Suryopranoto's Customer Relations Management are the focus of the research. This research uses a qualitative descriptive method. The theories used in this research are Public Relations theory, Two way symmetric model, Customer Relations Management theory. Data collection techniques through interviews and documentation. The validity technique used is source triangulation. The results of this research indicate that the Customer Relations Management activities carried out by Mitsubishi Suryopranoto were successful in retaining customers through implementing special programs, improving service quality, and handling customer complaints. These activities produce customer satisfaction so that they can retain customers.